Blood and salivary-gland BAFF-driven B-cell hyperactivity is associated to rituximab inefficacy in primary Sjögren's syndrome. (February 2016) - Cornec, Divi; Costa, Sebastian; Devauchelle-Pensec, Valérie; Jousse-Joulin, Sandrine; Marcorelles, Pascale; Berthelot, Jean-Marie; Chiche, Laurent; Hachulla, Eric; Hatron, Pierre-Yves; Goeb, Vincent; Vittecoq, Olivier; Saraux, Alain; et al.
Abstract: Objectives: To determine whether B-cell markers (blood and minor salivary gland [SG] B-cell depletion [BCD], autoantibodies, B-cell-activating factor [BAFF]) are associated with clinical response to rituximab in patients with primary Sjögren's syndrome (pSS). Methods: 45 patients with pSS were included: in group I, 14 received low-dose rituximab (two 375-mg/m 2 infusions) in an open-labelled study; in group II, 17 received full-dose rituximab (two 1000-mg infusions) and 14 received a placebo in a randomized, controlled study. The proportion of SG B cells was assessed using pixel-based software analyses of digitized double-immunostained (CD3/CD20) whole SGs. Response was defined at week-24 according to the Sjögren's Syndrome Responder Index (SSRI)-30. Results: Response rate was 50% in both groups of rituximab-treated patients. Duration of blood BCD was similar in both groups despite the difference in rituximab dosage, and was highly correlated with residual serum-rituximab levels at week-16. SG B-cell dynamics mirrored blood B-cell levels, with a drastic decrease in SG B-cells at week-12 (group I), but an increase in ∼50% of patients in group II by week-24, in whom blood B cells had already returned. Duration of BCD was not associated with the clinical response, but responders had lower baseline proportions of SG B cells. Baseline serum BAFF level was correlated with the proportion of SG B-cells and other B-cell-activation markers, and was associated with the clinical response with higher levels in non-responders. Conclusions: In pSS, half of the patients display an intense BAFF-driven B-cell activation and do not respond to a single course of rituximab. Highlights: The clinical response to rituximab is highly heterogeneous in pSS. The pattern and timing of B-cell depletion is similar in blood and salivary glands. The duration of B-cell depletion is not associated with rituximab clinical efficacy. BAFF drives B-cell hyperactivity and resistance to rituximab in half of the patients.